Mobbing and Suppression: Footprints of Their Relationships - Brian Martin; Florencia Peña Saint Martin (Social Medicine Publication Group, 2024)
Aims: two important processes involving the exercise of power are mobbing and suppression of dissent. These are examined, compared and contrasted with the aim of expanding the understanding of organisational and professional negative dynamics. Methods: The characteristic features and patterns of mobbing and suppression of dissent are examined. Areas of overlap and difference are noted and discussed. Results: Dissent is a challenge to a dominant group or set of ideas, and often met with various reprisals, such as ostracism, harassment and censorship: dissenters are frequently subject to mobbing. However, there are some different processes involved. Some targets of mobbing are chosen because they are different, not because they are challenging an orthodoxy. Some forms of suppression do not involve mobbing: a dissident researcher might be denied jobs and have publications and grant applications rejected, but not be subject to any personal abuse. The result is that individuals or ideas may be marginalised without the usual features of mobbing. Mobbing and suppression of dissent overlap with reprisals against whistleblowers. Some whistleblowers are mobbed or suppressed. However, suppression can occur without whistleblowing, for example when researchers obtain results unwelcome to powerful groups. Conclusion: A greater understanding of processes of suppression can assist mobbing researchers understand the wider dimensions of power used by groups against opponents. Mobbing sometimes is used to suppress. They both share many strategies, but nonetheless they are different. Key words: mobbing, suppression of dissent, whistleblowers